COMPARISON OF SPORTS MASSAGE AND ICE COMPRESS ON CHANGES IN THE DURATION OF DECREASING THE PAIN VALUE OF HAMSTRING MUSCLE DOMS RUGBY ATHLETES PON JABAR TO XXI: PERBANDINGAN SPORT MASSAGE DAN ICE COMPRESS TERHADAP PERUBAHAN DURASI PENURUNAN NILAI NYERI DOMS OTOT HAMSTRING ATLET RUGBY PON JABAR KE XXI - Diki Permadi Pratama; Fransiska Xaveria Hargiani; Angria Pradita; Sartoyo Sartoyo (Jurnal Kesehatan Hesti Wira Sakti, 2024)
Delayed Onset Muscle Soreness (DOMS) is muscle discomfort that varies from mild tension to severe pain that can impair function. DOMS pain is caused by the accumulation of metabolic waste in the muscle, such as lactic acid, as well as extracellular fluid that irritates the sensory fiber endings. Physiotherapy modalities, such as Sports Massage and Ice Compress, can be applied to prevent and treat DOMS. This quasi-experimental study used a two group pre-post test design that compared the effect of sports massage and ice packs on changes in DOMS pain values. This research was conducted at the Yonzipur 9 Ujung Berung field, Bandung City, with a population of 24 rugby athletes PON XXI JABAR, sampling using the total sampling method which was divided into 2 groups, namely (1) sports massage and (2) ice compresses with each group totaling 12 respondents. The measuring instrument used to assess the DOMS pain scale is the Numeric Rating Scale (NRS). The results of the study based on the median of the sport massage group before and after with a value of 7.5 and 4; the ice pack group showed a median value of 5 and 3 (before and after). Based on the Mann-Whitney analysis hypothesis test, the p value = 0.269> 0.05. It can be concluded that there is no significant difference in the effectiveness of the two methods. These findings indicate that Sports Massage and Ice Compress have comparable effectiveness in the management of DOMS muscle pain in athletes after intensive physical activity.